Analisis Partisipasi Anggaran dan Transparansi Terhadap Pengelolaan Keuangan Pada BPKD Kabupaten Bireuen - Jamaluddin Jamaluddin; Muhammad Iqbal; Adri Patria; Zakaria Yahya; Taufik Jahidin (Forum Kerjasama Pendidikan Tinggi, 2022)
This study aims to determine the effect of budget participation and transparency on financial management at the BPKD of Bireuen Regency, either partially or simultaneously. The population of this study were all civil servants at the Bireuen District BPKD with a sample of 79 employees. The sampling technique in this study used a saturated sampling technique or census method. The methodology in this study uses the quantitative method. From the results of this study it was found that there is an effect of budgetary participation (X1) on financial management (Y) in BPKD Bireuen Regency.